Pengaruh Kemajuan Teknologi Terhadap Pola Hidup Manusia - Al-Kansa, Bunga Bhagasasih; Iswanda, Mila Lisnadiani; Kamilah, Nurul; Herlambang, Yusuf Tri (Indo-MathEdu Intellectuals Journal, 2023)
This research shows the importance of technology in our lives and how it has also become an integral part of communication in our lives. There are several things the impact found from technological advances on human life. By using literature research methods, namely analyzing as many as 30 scientific journals, researchers try to analyze the influence of technological advances on human life patterns in social and cultural, political, and economic aspects. The results of the study explained that there are several changes in human life patterns due to the influence of technological advances, both in the socio-cultural, political, educational, and economic fields.